The Mosque as a Resilient Model: Adaptation in Social, Spatial, and Environmental - Bramasta Putra Redyantanu (DIMENSI: Journal of Architecture and Built Environment, 2026)
The Amahami Floating Mosque in Bima, Indonesia was analyzed as an example of resiliency in multi-dimensional adaptation through architecture and how this type of approach may provide a future path forward for sustainability, durability and efficiency with respect to modern mosque architecture influenced by local contexts. This research demonstrates three overall areas of essential integrative adaptation: social, spatial and environmental. With regards to social adaptation, the study emphasized the importance of community involvement beyond that of worship in order to preserve the identity of Bima as an architectural region; with spatial adaptation, the Muslim community incorporated the floating structure of the mosque into their site conditions as well as optimizing waterfront usage; and with environmental adaptation, the design of the mosque incorporated modular construction and structure to maximize the efficiency of material usage as well as to enhance natural light quality and ventilation. In conclusion, using these three integrative adaptations enables the mosque to be viewed as a resilient architectural prototype that links heritage with sustainability in an effort to promote adaptive design. While adaptive architecture is not limited to mosques serving only as places of worship, the results from this study suggest that there exists an opportunity to combine urban planning, eco-awareness and long-term resiliency.